The Illusion of Integrating Customary Law into Indonesia’s Contract Law System on the Communal Sanctions Policy Forum - I Wayan Wahyu Wira Udytama; Mella Ismelina Farma Rahayu; I Wayan Gde Wiryawan (Journal of Human Rights, Culture and Legal System, 2026)
The Indonesian legal system is characterized by pluralism, where customary law exists alongside formal national law. Although customary law is normatively recognized, its integration into the national contract law system remains limited. This study aims, first, to analyze the normative integration of customary law and contract law in Indonesia; second, to compare the practice of customary law integration in Indonesia with Malaysia; and third, to formulate an ideal model for integrating customary law and contract law systems in the context of communal sanctions. The research employs normative legal methods with a threefold analytical approach are statutory, conceptual, and comparative. The findings indicate that, first, the integration of customary law into Indonesia’s contract law system is still primarily normative and not operational, as reflected in the application of the kasepekang sanction, which demonstrates a dualism between communal customary law and individualistic national contract law, resulting in legal uncertainty and potential injustice. Second, comparative analysis with Malaysia shows that although both countries recognize customary law, Indonesia lacks adequate operational mechanisms, whereas Malaysia implements constitutional, legislative, and judicial approaches that are more effective in contractual practice. Third, the ideal integration model in Indonesia requires transforming communal sanctions into mechanisms that are transparent, proportional, and restorative, aligned with human rights principles and contractual justice.